(untitled) (Global Journal of Science Frontier Research, 2018)
Leek (Allium ampeloprasum var. porrum L.) is one of the Allium vegetable crop growing in Ethiopia. However; the production and productivity of leek is not as such expected because of lack of appropriate planting space and ideal variety for the specific areas. Hence, a field experiment was carried out to determine the effect of plant spacing on three leek varieties at Areka in Southern Ethiopia. Factorial combinations of three leek varieties (Carentan Giant, Lancelot and Dawn Giant) with three inter-row spacing (20, 30 and 40 cm) and two intra-row spacing (10 and 15 cm) were laid out in a randomized complete block design with three replications. All Phenological, growth, yield components and yield parameters were recorded meticulously for necessary statistical data analysis. The revealed data indicated that days to 90% physiological maturity, leaf length, leaf width, leave number per plant, plant height, dry matter weight, biological yield and total pseudo stem yield were significantly affected by the main effect of variety, inter- and intra-row spacing. As the inter- and intra-row spacing increases the days to 90 % physiological maturity and leaf number per plant increases whereas biological and pseudo stem yield decreases. Variety ’Dawn (454.82 kg ha -1 ) and ’Lancelot’ (427.93 kg ha -1 ) had the highest biological yield whereas variety Carentan Giant had the lowest biological yield (147.90 kg ha -1 ). Likewise, variety ’Dawn Giant’ at 15 cm intra-row spacing gave the highest number of leaf width while variety Carentan Giant at 10 cm intra-row spacing gave the lowest. From this, it could be concluded that leek varieties (Carentan Giant, Lancelot’ and ’Dawn Giant’) could be planted at optimum spacing of 20 cm x 10 cm at Boloso bombe area to attain maximum yield though it is done in one season and location.